Caring of a person with a cardiovascular disease in situation that generates feelings of loss, threat, fear, or death (2010)
People living with cardiovascular disease find themselves permanently affected by uneasiness, disfunctionality and the feeling it causes. This situation creates changes in the patient's self-esteem, losses, mourning for these losses, changes in their lifestyle and the perception of death; this scenery is part not only of the individual, but it also involves the family and his/ her social environment. The purpose of this article is to review the types of losses, the stages of the mourning process, some considerations about death, the phasic process of dying suggested by Elizabeth Kubler Ross and the difficulties faced by nursing personnel, the person suffering the cardiovascular disease and his/ her family to cope with it. Death as the ending point of existence and a natural happening in the life of human beings, is one of the everyday phenomena which nursing personnel have to face. Its approach has emotional, spiritual and cultural implications; thus, strategies to face it are suggested for the nursing personnel, aimed at the person caring for the patient suffering cardiovascular disease and who experiences feelings of loss and threat or fear of death.